Article Review: Evaluation of Anti-Tuberculosis Drug Therapy Compliance in Adult Patients at Several Hospitals in West Java - Septiyadi; Elin Yulinah Sukandar (Jurnal FARMASIMED (JFM), 2026)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis, with the lungs as the primary site of infection, although other organs can also be affected. To date, tuberculosis control still faces various challenges, particularly related to the long duration of treatment, which can last for months. This long duration of therapy often results in decreased patient compliance in taking medication regularly. This low compliance directly contributes to treatment failure, an increased risk of relapse, and the potential for drug resistance. Furthermore, given the contagious nature of pulmonary tuberculosis, patient non-compliance also increases the risk of disease spread in the community. This study aims to describe the compliance profile of pulmonary tuberculosis patients undergoing anti-tuberculosis therapy in several hospitals in West Java Province. The method used is descriptive, examining variations in patient compliance levels based on available data. The results show significant variation in the level of compliance with anti-tuberculosis medication in the studied hospitals, ranging from 12.5% ​​to 92.8%. This variation indicates differences in factors that influence compliance, such as support from healthcare workers, patient understanding, and access to healthcare services. This study emphasizes the importance of targeted interventions to improve patient adherence to support successful therapy, accelerate the healing process, and sustainably reduce the rate of tuberculosis transmission in the community. Efforts to improve adherence can be achieved through comprehensive health education, strengthening treatment monitoring systems, and involving families in patient support. Furthermore, innovative community-based services have the potential to improve access and quality of treatment, resulting in more optimal and sustainable long-term therapy outcomes for all pulmonary tuberculosis patients.